Prolonged Amphetamine Exposures Increase the Endogenous Human Dopamine Receptors 2 at the Cellular Membrane in Cells Lacking the Dopamine Transporter - Nawaratne, Vindhya; McLaughlin, Sean P.; Mayer, Felix P.; Gichi, Zayna; Mastriano, Alyssa; Carvelli, Lucia (Frontiers in Cellular Neuroscience, 2021)
The dopamine 2 receptors (D2R) are G-protein coupled receptors expressed both in presynaptic and postsynaptic terminals that play an important role in mediating the physiological and behavioral effects of amphetamine (Amph). Previous studies have indicated that the effects of Amph at the D2R mainly rely on the ability of Amph to robustly increase extracellular dopamine through the dopamine transporter (DAT). This implies that the effects of Amph on D2R require the neurotransmitter dopamine. However, because of its lipophilic nature, Amph can cross the cellular membrane and thus potentially affect D2R expression independently of dopamine and DAT, e.g. in post-synaptic terminals. Here we used an in vitro system to study whether Amph affects total expression, cellular distribution, and function of the human D2R (hD2R), endogenously expressed in HEK293 cells. By performing Western blot experiments, we found that prolonged treatments with 1 or 50 µM Amph cause a significant decrease of the endogenous hD2R in cells transfected with human DAT (hDAT). On the other hand, in cells lacking expression of DAT, quantification of the hD2R-mediated changes in cAMP, biotinylation assays, Western blots and imaging experiments demonstrated an increase of hD2R at the cellular membrane after 15-hours treatments with Amph. Moreover, imaging data suggested that barbadin, a specific inhibitor of the βarrestin-βadaptin interaction, blocked the Amph-induced increase of hD2R. Taken together our data suggest that prolonged exposures to Amph decrease or increase the endogenous hD2R at the cellular membrane in HEK293 cells expressing or lacking hDAT, respectively. Considering that this drug is often consumed for prolonged periods, during which tolerance develops, our data suggest that even in absence of DAT or dopamine, Amph can still alter D2R distribution and function.